TR35 Exerts Anti-tumor Effects by Modulating Mitogen-Activated Protein Kinase and STAT3 Signaling in Lung Cancer Cells - Shi, Zhiyong; Gao, Yang; Feng, Lifeng; Tian, Wencong; Dou, Zhihua; Liu, Chen; Liu, Jie; Xu, Yang; Wang, Yachen; Yan, Jie; Wu, Qiang; Li, Jing; et al. (Frontiers in Cell and Developmental Biology, 2021)
Cancer is a complex disease extremely dependent on its microenvironment and is highly regulated by a variety of stimuli inside and outside the cell. Evidence suggests that active camel whey fraction (TR35) confer anti-tumor effects in non-small cell lung cancer (NSCLC). However, its exact mechanisms remain elusive. Here, we investigated the mechanisms underlying suppression of NSCLC cell growth and proliferation by TR35. Treatment of A549 and H1299 cells with TR35 suppressed their growth and enhanced apoptosis, as revealed by CCK-8, colony formation and flow cytometric analyses. We find that TR35 suppresses tumor growth in a xenograft nude mouse model without losses in body weight. RNA-seq and KEGG pathway analyses showed that the DEGs were enriched in mitogen-activated protein kinase (MAPK) and Jak-STAT signaling pathways. After test the key factors’ activity associated with these pathways by Immunohistochemical (IHC) staining and western blotting, the activation of JNK phosphorylation and inhibition of p38 and STAT3 phosphorylation was observed both in TR35 treated lung cancer cell and tumor tissue. Taken together, these results showed that TR35 play a significant role in the NSCLC progression in the tumor microenvironment via MAPK and Jak-STAT signaling, highlighting TR35 as a potential therapeutic agent against lung cancer.